Reframing the Roman Economy New Perspectives on Habitual Economic Practices - Van Limbergen, Dimitri; Hoffelinck, Adeline; Taelman, Devi. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book focuses on those features of the Roman economy that are less traceable in text and archaeology, and as a consequence remain largely underexplored in contemporary scholarship. By reincorporating, for the first time, these long-obscured practices in mainstream scholarly discourses, this book offers a more complete and balanced view of an economic system that for too long has mostly been studied through its macro-economic and large-scale - and thus archaeologically and textually omnipresent - aspects. The topic is approached in five thematic sections, covering unusual actors and perspectives, unusual places of production, exigent landscapes of exploitation, less-visible products and artefacts, and divergent views on emblematic economic spheres. To this purpose, the book brings together a select group of leading scholars and promising early career researchers in archaeology and ancient economic history, well positioned to steer this ill-developed but fundamental field of the Roman economy in promising new directions. Dimitri Van Limbergen is a researcher at Ghent University, Belgium. His main areas of study are Roman archaeology and economic history. Adeline Hoffelinck is a researcher at Ghent University, Belgium. She researches the transformation of commercial infrastructure in Roman cities during their urbanization. Devi Taelman is a researcher at the Vrije Universiteit Brussel, Belgium. He is interested in the study of the economy of ornamental stones used in antiquity, and in human-environment interactions in Roman Antiquity.
Chapter 1: Pathways to reframing the Roman economy: from uniformity to diversity? -- Part I Unusual actors, attitudes and perspectives -- Chapter 2: Textile economy in the Veneto Region (North-Eastern Italy): a textile tools oriented spatial approach -- Chapter 3: Craftsmen and shopkeepers serving the army: the example of the colony of Lugdunum (1st century AD) -- Part II Unconventional loci of production -- Chapter 5: Roman metallurgic production in the Veneto region between urban and rural contexts -- Chapter 6: Pigs in the city, bees on the roof: intra-urban animal husbandry and butchery in Roman Spain -- Chapter 7: Olive Oil Production and Economic Growth in the Roman Provinces: the Peculiar Case of Volubilis in Mauretania Tingitana -- Chapter 8: Roman road stations in Gallia Cisalpina: an archaeological approach to elusive central places -- Chapter 9: Ephemeral Economies? Investigating Roman wetland exploitation in the Pontine marshes (Lazio, Central Italy) -- Chapter 10: Settling the Salinaria? Evaluating site location patterns of Iron Age and Roman salt production in northern Gaul -- Chapter 11: Ollae, cistulae, cadi, utres, cupae and other intangible vessels in the Roman economy. Some case studies -- Part V Revising traditional narratives -- Chapter 12: Reconstructing economic rural landscapes. The case of southern Etruria -- Chapter 13: Ancient Indian Ocean Trade and the Roman Economy. .
Keywords: Economic history; Europe-History-To 476.; Archaeology; Economic History; History of Ancient Europe; Archaeology